The Status of Children Outside of Marriage and Its Relevance to the Reform of Islamic Family Law in Indonesia - Ummil, Ummil Fadhliyah Soraya; Nisa, Umi Khoirun; Maryani; Samin Batubara (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research discusses the Status of Children Outside of Marriage and its Relevance to the Renewal of Islamic Family Law in Indonesia. This research aims to find out specifically how the status of children outside of marriage and its relevance to the reform of Islamic Family Law in Indonesia. The method used in this research is the method of collecting data through library research. Data is collected by collecting information from various sources of literature, such as books, journals, magazines, and so on. From this research, it can be concluded that the scholars agree that children born out of wedlock have family ties both with the mother and her family. This is also the case in the laws and regulations governing marriage law in Indonesia which stipulate that the only civil relationship of children born out of wedlock is with the mother and her family. Nevertheless, the plaintiff permitted the Constitutional Court to conduct a judicial review, especially to ensure that her child was given permanent legal status and accepted by the defendant's family. After the respondent disputed the existence of the child and ignored the child's civil rights, including payment of monthly living expenses and school fees, the plaintiff was forced to take legal action. Thus, the Constitutional Court decided to partially grant the petitioners' claims based on the reasoning of the Panel of Judges. It was an extraordinary ijtihad when the Constitutional Court issued a new ruling on the status of children born out of wedlock. The Constitutional Court's decision is supported by arguments that are in the public interest (al-mashlahah al-'ammah), including protecting the future of children and providing a deterrent effect on men who have free sex so that adultery does not become commonplace. At least today, we can observe that legal progress in Indonesia also considers vulnerable groups, especially children.